2007
DOI: 10.1002/cvde.200606546
|View full text |Cite
|
Sign up to set email alerts
|

Radical Enhanced Atomic Layer Deposition of Titanium Dioxide

Abstract: Titanium dioxide films are grown with radical-enhanced atomic layer deposition (RE-ALD) from titanium isopropoxide and oxygen radicals at between 50 and 300°C on silicon, glass, platinum, and RuO 2 surfaces. Additionally, the films are grown on polymers and natural fibers at 50°C. The oxygen radicals are produced by dissociating molecular oxygen with a remote microwave plasma discharge. Purified argon is used as the carrier and purge gas. Growth rate saturation and conformal growth are observed, and thus the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 56 publications
7
40
0
Order By: Relevance
“…Consequently, this can lead to higher growth per cycle values. 31,32,40,58,60,134,154,187,207,208,229,233,254,259,261,274,294 Moreover, the plasma can be switched on and off very rapidly, which enables fast pulsing of the plasma reactant species 255,273,274,293,295 and reduced purge times (depending on the gas residence time in the reactor). 46,60 The latter is especially important for the ALD of metal oxides at low temperatures (room temperature up to 150 C), where purging of H 2 O, in the case of thermal ALD, requires excessively long purge times and, therefore, long cycle times.…”
Section: E Increased Growth Ratementioning
confidence: 99%
“…Consequently, this can lead to higher growth per cycle values. 31,32,40,58,60,134,154,187,207,208,229,233,254,259,261,274,294 Moreover, the plasma can be switched on and off very rapidly, which enables fast pulsing of the plasma reactant species 255,273,274,293,295 and reduced purge times (depending on the gas residence time in the reactor). 46,60 The latter is especially important for the ALD of metal oxides at low temperatures (room temperature up to 150 C), where purging of H 2 O, in the case of thermal ALD, requires excessively long purge times and, therefore, long cycle times.…”
Section: E Increased Growth Ratementioning
confidence: 99%
“…A model was proposed for the ALD precursors' adsorption on surface and diffusion into the subsurface of polymers without active groups [19], and it was found that the process temperature significantly affected the interface between the deposition layer and the substrate [26,27]. There are some reports on the deposition of metal oxides by ALD on PP substrates but most studies are focused on the deposition of metal oxides, mainly Al 2 O 3 , on nonporous PP films [19,[27][28][29][30]. One work was reported on the ALD deposition of Al 2 O 3 on porous PP membranes with the purpose to improve the wettability of electrolyte solutions and the thermal stability of the PP membrane in the use of lithium ion batteries [31].…”
Section: Introductionmentioning
confidence: 98%
“…8,9 A variety of synthesis techniques have been used, including chemical vapor deposition ͑CVD͒, 8,10 sputtering, 1,2 plasma-enhanced CVD ͑PECVD͒, 11,12 and atomic layer deposition ͑ALD͒. 4,5,[13][14][15][16][17][18] Emerging applications demand improved quality and control. ALD imparts digital control over film thickness and composition, as well as exceptional film quality.…”
mentioning
confidence: 99%